The Social Rationality of Theological Discourse - Martin, Terence J. (Horizons, 1986)
Drawing lessons from literary dialogues on religious issues, this essay offers a rhetorical and hermeneutical analysis of the workings and achievements of theological discourse. The rationality proper to theological discourse is found to be a function of interlocutors' communicative actions and reactions, describing the social processes by which speakers sustain common space and time for persuasion and understanding. Standards of rationality are idiosyncratic not simply to individual cultural-linguistic frameworks, but to public, dialogical situations which speakers must create and sustain in their communicative interaction.